Attitude of the Western states towards Lithuania About the Doctoral Thesis and a it Defence of Ramojus Kraujelis "Attitude of the Western states towards occupation and annexation of Lithuania in the period of 1940-1953") - Jakubčionis, Algirdas (Lietuvos istorijos studijos, 2006)
-